Micro gas turbine: Developments, applications, and key technologies on components - Jingqi Li; Yulong Li (Propulsion and Power Research, 2023)
Owing to their precedent characteristics, micro gas turbines (MGTs) have been favored as popular power machinery in plenty of energy systems such as distributed energy systems, range extenders, solar power generations, fuel cell systems and individual power supplies. Their specific features essentially include but are not limited to strong fuel adaptability, low emissions, flexible structure, and easy maintenance. Over the past 20 years, various types of MGTs have been developed. Classical and forward-looking technologies have been employed in the design and production of MGTs and their components. Among them, fully radial flow structures, gas lubricated bearings and efficient recuperators are typical approaches to enhance the overall performance and compactness, however, the exploitation of ceramic based materials and intelligent algorithms in component design can also assist in improving the performance. The applications of MGTs have been expanded to many fields, and the research on related components has also made new progress. Due to the time frame, there is no systematic summary of the latest relevant research, so it is essential to have a comprehensive understanding of the applications of MGTs and their pertinent components. This paper aims to present a comprehensive review on MGTs, covering the development status, applications, factors of performance and representative explorations of their components. Some investigations regarding the characteristics of commercial MGTs are also conducted. Applications in distributed energy, range extenders, solar generations, and fuel cell systems are distinctly introduced. Recent research work on compressors, turbines, combustors, recuperators, and rotor systems are reviewed and analyzed. The technologies and methods associated with materials, manufacturing, and cycles beneficial to the future development of MGTs are also explained and discussed in some detail.